PRE-COMMODIFICATION OF SIGALEGALE: BETWEEN FOLKLORE AND THE PAPURPUR SAPATA RITUAL IN SIMANINDO DISTRICT - Yehezkiel Pardosi; Mauly Purba; Thyrhaya Zein; Septiana Wahyuningsih (International Journal of Cultural and Social Science, 2026)
This study aims to examine the existence of Sigalegale in its pre-commodification phase and to analyze the dynamics of cultural transmission associated with it in Simanindo District, Samosir Regency. Employing a qualitative approach with an ethnographic model, data were collected through in-depth interviews, observation, and documentation involving Sigalegale performance managers and tourism destination managers. The findings reveal that prior to its transformation into a tourism performance, Sigalegale possessed two main entities within Batak Toba culture: as folklore and as the central figure in the papurpur sapata ritual. This ritual is associated with deaths occurring under the condition of mate punu and is rooted in the belief system of hasipelebeguan. However, field findings indicate that contemporary performance managers understand Sigalegale solely as folklore and are unaware of its former ritual function. This situation reflects a disruption and selectivity in cultural transmission, in which narrative elements are preserved while ritual knowledge becomes marginalized. Contributing factors to this condition include the non-inclusive and rare nature of the papurpur sapata ritual, as well as the introduction of religion to the Batak region, which led to the prolonged suspension of ancestral ritual practices. This study concludes that the transformation of Sigalegale from a pre-commodified cultural practice into a tourism performance represents not only a functional shift, but also a process of disrupted and selective cultural transmission shaped by social, religious, and historical factors.